2013
DOI: 10.1063/1.4792664
|View full text |Cite
|
Sign up to set email alerts
|

Self-doping and the role of oxygen vacancies in the magnetic properties of cubic BaFeO3−δ

Abstract: Although barium ferrate is known to accommodate a range of oxygen stoichiometries, which give rise to distinct magnetic properties, the mechanism underlying this coupling is not clearly understood. In order to address this issue, the electronic and magnetic properties of pseudocubic BaFeO3−δ with 0 ≤δ≤ 0.5 were studied using density functional theory. The present results attest the influence of the oxygen content on the magnetic order: for high oxygen content, the magnetic interactions are predominantly ferrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 18 publications
9
31
0
Order By: Relevance
“…The FM spin state was identified as the ground state, this is consistent with previous DFT+U studies of parallel magnetic orderings of cubic BFO and SOFC operating conditions. 43,57 However, experimental analysis of the cubic stoichiometric BFO, identified an A-AFM type spin-spiral state below 111K, and FM above. 22 In relation to this, other DFT work studied a more precise helical spin ordering and found an However, the same study also identified a small energy barrier (0.017 meV per unit cell) for the transition from AFM to FM structures.…”
Section: Oxygen Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The FM spin state was identified as the ground state, this is consistent with previous DFT+U studies of parallel magnetic orderings of cubic BFO and SOFC operating conditions. 43,57 However, experimental analysis of the cubic stoichiometric BFO, identified an A-AFM type spin-spiral state below 111K, and FM above. 22 In relation to this, other DFT work studied a more precise helical spin ordering and found an However, the same study also identified a small energy barrier (0.017 meV per unit cell) for the transition from AFM to FM structures.…”
Section: Oxygen Deficiencymentioning
confidence: 99%
“…Next, the electronic structure of BFO was explored in the projected density of states (PDOS), Figure 3, which revealed a nearly half-metallic electronic structure with a high Fe spin state; this is consistent with previous DFT+U studies. 57 …”
Section: Oxygen Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it is difficult to synthesize stoichiometric cubic BFO because the high valence Fe 4+ is not favorable in this system since the Fe 3d band energy is lower than O 2p band, introducing a negative ligand to metal charge transfer 50 energy. 13 Although phase transition of the mixed phase to pure cubic structure is observed at around 900 °C, 14 application of this material at intermediate temperature is not feasible because the material performance substantially decreases due to the presence of the vacancy-ordered monoclinic phase. Nevertheless, several 55 synthesis methods have been used to obtain phase-pure cubic BFO at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For the FM order and experimental lattice parameter of the cubic BFO, the calculated magnetic moment varies between 3.0 µ B and 3.4 µ B per f.u., 15,16 depending on the model approximation used to treat the exchange-correlation effects. According to the ab initio investigation by Ribeiro et al 17 the FM solution in the stoichiometric BFO is energetically favorable against the possible AFM configurations while the FM moment is about 3.6 µ B . A helical magnetic ordering in BFO, which is usually discussed in the context of SrFeO 3 and CaFeO 3 , 18 has been investigated from first principles by Zhi Li et al 19,20 The authors anticipate that the G-type helical solution can be fixed, keeping the reduced volume and, simultaneously, using the Hubbard parametrization which treats electronic correlations beyond the standard of the local density approximation.…”
Section: Introductionmentioning
confidence: 99%